Down‐conversion materials for organic solar cells: Progress, challenges, and perspectives: Photovoltaics: Special Issue Dedicated to Professor Yongfang Li. Issue 3 (26th February 2022) - Datt, Ram; Bishnoi, Swati; Lee, Harrison Ka Hin; Arya, Sandeep; Gupta, Sonal; Gupta, Vinay; Tsoi, Wing Chung
Abstract: Organic solar cells (OSCs) in terms of power conversion efficiency (PCE) and operational lifetime have made remarkable progress during the last decade by improving the active layer materials and introducing new interlayers. The newly developed wide bandgap organic donor and low bandgap acceptor molecules covered the absorption from the visible to the near‐infrared region. Whereas the incident high energy region (UV) is not in favor of OSCs. Its absorption causes thermalization losses and photoinduced degradation, which hinders the PCE and lifetime of OSCs. Recently, lanthanide and non‐lanthanide‐based down‐conversion (DC) materials have been introduced, which can effectively convert the high‐energy photons (UV) to low‐energy photons (visible) and resolve the spectral mismatch losses that limit the absorption of OSCs in high energy incident spectrum. Furthermore, the DC materials also protect the OSCs from UV‐induced degradation. The DC materials were also proposed to cross the Shockley‐Queisser efficiency limit of the solar cell. In this review, the need for DC materials and their processing method for OSCs have been thoroughly discussed. However, the main emphasis has been given to developing lanthanides and non‐lanthanides‐based DC materials for OSCs, their applications, and their impact on photovoltaic device performance, stability, and future perspectives. Abstract : The article demonstrates an overview of the lanthanides and non‐lanthanides‐based down‐conversion materials in improving the photostability and performance of organic solar cells (OSCs) by the conversion of incident high energy to low energy photons. It establishes an application link between luminescent materials and OSCs, which can be a technique to cross the solar cells Shockley–Queisser limit.